Surgeons' workload assessment during indocyanine-assisted deep endometriosis surgery using the surgery task load index: The impact of the learning curve - Spagnolo, Emanuela; Cristóbal Quevedo, Ignacio; Gortázar de las Casas, Sara; López Carrasco, Ana; Carbonell López, Maria; Pascual Migueláñez, Isabel; Hernández Gutiérrez, Alicia (Frontiers in Surgery, 2022)
Objective Assess the surgeons' workload during deep endometriosis surgery after ureteral ICG Design Prospective, consecutive, comparative, single-center study Population 41 patients enrolled to deep endometriosis surgery with ureteral ICG from January 2019 to July 2021 at La Paz University Hospital Methods Patients were divided into 2 groups: patients operated during the learning curve of ureteral ICG instillation and patients operated after the technique was implemented and routinely performed. After surgery, the SURG-TLX form was completed by the surgeons. We evaluated whether a workload reduction occurred. Main outcomes measures Surgeon's workload was measured using the SURG-TLX form, obtaining the total workload and 6 different dimensions (distractions, temporal demands, task complexity, mental demands, situational stress and physical demands) Results A significant positive correlation was found between surgical complexity and situational stress (p = 0.04). Mental demands (p = 0.021), physical demands (p = 0.03), and total workload (p = 0.025) were significantly lower when the technique was routinely performed. The mental demand, physical demands, and total workload perceived by the surgeons at the beginning of the implementation was higher (68 [39–72], 27 [11–46.5], 229 [163–240], respectively) than in the latter ones (40 [9–63], 11.5 [0–32.8], 152 [133.3–213.8], respectively). Distractions appeared to be higher in the latter surgeries (8.5 [0–27.8]) than in the first surgeries (0 [0–7]; p = 0.057). Conclusions Ureter ICG instillation prior to DE surgery significantly reduces the mental and physical demands and total workload of the surgeons in DE surgeries after overcoming the learning curve. Distractions appear to increase as surgical stress decreases.